Determination of urinary estrogen during pregnancy by gas chromatography and thin layer - Sobrevilla, Luis (2015)
We have studied the urinary excretion of estrogens in 15 normal term pregnant women by the method of gas chromatography and thin layer Wotiz and Chottoraj, with the following results: Estrone. 1.90 + 0.73 mgm / 24 hours Estradiol: 0.56 ± 0.20 mgm. / 24 hours. Estriol: 27.2 + 9.2 mgm / 24 hours.. (Average ± standard deviation). The method is described and the clinical application of the findings discussed estrogen during pregnancy. In a case of hydatidiform mole, chorionic gonadotropin high with low estrogen excretion was found, estriol decreased the very being.